Short screening for diabetic foot disease in an omani population at Al-Dahira, Sultanate of Oman: A cross-sectional study - Sabria A L Marshoudi; Fatma Ahmed; Syed Wali Peeran; Amru AlBurji; Khalid Al-Kalbani; Sabri M Yousf (Wolters Kluwer Medknow Publications, 2021)
Objective: This study aims to implement a short primary health-care screening program for diabetic foot disease (DFD) in diabetic patients and to detect the prevalence and predictors of the DFD, to determine their positive risk factors for DFD by identifying patients who have neuropathy or vascular disease, and to examine whether the predictors (neuropathy and vasculopathy) have a significant effect on DFD. Subjects and Methods: This study is a cross-sectional study conducted in different diabetic clinics located in health centers across Al-Dahira, Oman. A single, trained clinician from each health center was selected to complete the questionnaire. The sample was randomly selected among subjects already diagnosed as diabetic patients. The study was carried from July 2017 to September 2017. Diabetes mellitus (DM) patients (Type-1 and Type-2) can be affected by DFD. In Al-Dahira, Oman, both Type-I and Type-II DM visited the same clinics. The screening carried out consisted of sections dealing with information of the subjects including their smoking status, number of visits, and details about their diabetic status. A detailed examination of DF was carried over if present in the subjects. The areas that were screened for DF included skin assessment, structural examination of the DF, vascular assessment, neuropathy assessment, as well as DF ulcer assessment. Results: Out of 216 patients, the mean age was 60.56 years (standard deviation 12.74) with a range of 25 years to 97 years. Out of the total patients, there were (164 patients) 75.9% of cases are DFD. However, the prevalence of foot ulcer, gangrene, and amputations were 4.2%. Among the studied subjects, 65.9% had poor glycemic profile value. Most of the patients had a history of diabetes for more than 5 years. The results showed that the age (P = 0.038 < 0.05), physical activity (P = 0.034 < 0.05), and neuropathy (P = 0.33 < 0.05) had an association with DFD. Conclusions: A short primary health-care screening program for DFD in diabetic patients is considered a useful tool and a helpful method to increase the awareness of DFD at the community level. Further, it helps to evaluate the level of the patient's risk for prevention and further management.